2013
DOI: 10.5194/hess-17-2905-2013
|View full text |Cite
|
Sign up to set email alerts
|

Experiences in using the TMPA-3B42R satellite data to complement rain gauge measurements in the Ecuadorian coastal foothills

Abstract: Abstract. At present, new technologies are becoming available to extend the coverage of conventional meteorological datasets. An example is the TMPA-3B42R dataset (research -v6). The usefulness of this satellite rainfall product has been investigated in the hydrological modeling of the Vinces River catchment (Ecuadorian lowlands). The initial TMPA-3B42R information exhibited some features of the precipitation spatial pattern (e.g., decreasing southwards and westwards). It showed a remarkable bias compared to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…It is well reported that the accuracy of satellite-based precipitation products is dependent on precipitation variability, topography, and climate [6][7][8][9][10]. A large number of studies have evaluated the performance of 3V42V6 in many parts of world [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It is well reported that the accuracy of satellite-based precipitation products is dependent on precipitation variability, topography, and climate [6][7][8][9][10]. A large number of studies have evaluated the performance of 3V42V6 in many parts of world [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The monthly precipitation estimate, due to its relatively long series and high correlation with ground observation, is widely discussed in bias correction studies [48][49][50][51]. In this study, we adopted the bias correction method of Arias-Hidalgo et al [48] to improve the 3B42V7 rainfall product in the Hexi region. This method assumes that the bias of 3B42V7 at a specific grid is similar to those nearest grid with a station inside it.…”
Section: Bias Correction Methodsmentioning
confidence: 99%
“…Due to their high spatio-temporal resolution, the TMPA-3B42 v7 and 3B42RT data products daily temporal resolution and 0.25° [approx. 27.83 km] spatial resolution, with global coverage from 50° N to 50° S: [daily temporal resolution and 0.25° [approx. 27.83 km] spatial resolution, with global coverage from 50°N to 50°S: 10] were selected for evaluation as suitable drivers for the model.…”
Section: Trmm Datamentioning
confidence: 99%
“…27.83 km] spatial resolution, with global coverage from 50° N to 50° S: [daily temporal resolution and 0.25° [approx. 27.83 km] spatial resolution, with global coverage from 50°N to 50°S: 10] were selected for evaluation as suitable drivers for the model. These data were downloaded from the NASA data server (disc.sci.gsfc.nasa.gov) for the period 2003-2014.…”
Section: Trmm Datamentioning
confidence: 99%
See 1 more Smart Citation